FIRST REPORT ON THE CO-EXISTENCE OF AMCROSPORIDIAN WITH LAMERIN BREED OF THE SILKWORM, BOMBYX MORI L. - BHAT, SHABIR AHMAD; NATARAJU, B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2007)
In the present study, the co-existence of a microsporidian with Lamerin breed of the silkworm, Bombyx mori L. has been investigated. This investigation has produced information on the influence of microsporidian on morphometric parameters of the breed. The microsporidian parasite transmits transovarially, causes disease, is not found to be an important factor that adversely influences the development of the host. Microsporidian parasite and Lamerin breed have a close relation with each other. Larvae developed from the eggs laid by female infected with microsporidian parasite were as normal as larvae developed from the eggs laid by healthy female. The infection showed no significant effect on development and health status during their life cycle.